Licensure of Pysicians - Edward H. Forgotson; Ruth Roemer; Roger W. Newman (Washington University Law Quarterly, 1967)
This Article examines the most significant features of state medical licensure laws: the scope of mandatory licensure, including the important question of authority for delegations of functions; the nature and role of state licensing agencies; qualifications for licensure candidates, including accreditation of medical schools; license registration and renewal, and reinstatement of lapsed licenses; recognition of licenses of other jurisdictions; and license suspension or revocation, and reinstatement of removed licenses.
Keywords: Physicians and surgeons